Interactions Between Body Iron and Obesity on Type 2 Diabetes in Chinese Adult. (29th May 2020) - Liu, Changfeng; Lyu, Quanjun
Abstract: Objectives: Limited information exists regarding the effect of interaction of obesity and body iron stores on type 2 diabetes. The aim of this study is to assess effect modification by obesity on the association between body iron stores and type 2 diabetes in Chinese adult. Methods: A total of 8337 adults aged 18 years old or above from CHNS in 2009 were included to investigate the association of TfR-F index and type 2 diabetes. Serum ferritin (SF), transferrin (TfR), soluble transferrin receptor (sTfR), and haemoglobin (Hb) were measured. Type 2 diabetes was defined as fasting glucose ≥7.0 mmol/L or current usage of antidiabetes medications. The logistic regression model was adopted to examine the health effects. The interaction effect was examined in a separate model by adding a multiplicative interaction term (i.e., BMI * each body iron parameters). Results: Interactions were found between SF/TfR and obesity on type 2 diabetes. The association between SF and type 2 diabetes was larger for obese adult than for those with normal/overweight, with odds ratios of 1.18 per 100 ng/mLfor increase (95% confidence interval [CI] = 1.08, 1.29). However, the association between TfR and type 2 diabetes was larger for obese adult than for those with normal/overweight, with odds ratios of 6.00 per 5 mg/L increase (95% CI = 1.58, 15.96).No significant interaction was observed between haemoglobin/sTfR and obesity on type 2 diabetes. Conclusions: Obesity amplifies the association of body iron stores and type diabetes in Chinese adults. Funding Sources: N/A.